Pengaruh Kecerdasan dan Love of Money Terhadap Persepsi Etis Mahasiswa Akuntansi - Ratih Manuari, Ida Ayu; Devi, Ni Luh Nyoman Sherina (E-Jurnal Akuntansi; Vol 30 No 11 (2020)DO - 10.24843/EJA.2020.v30.i11.p19, 2020)
This study aims to determine the effect of intellectual intelligence, emotional intelligence, spiritual intelligence, and love of money on the ethical perceptions of accounting students. The purpose of accounting education is to introduce students to values and ethical standards in the accounting profession. The importance of ethics in a profession makes the accounting profession focus its attention on the ethical perceptions of accounting students, as a starting point in increasing perceptions of the accounting profession. therefore, research on ethics in accounting students is needed. The sample was selected using nonprobability sampling method with a total sample of 75 respondents and used multiple linear regression analysis as a testing tool. The results showed that spiritual intelligence and love of money had a positive effect on the ethical perceptions of accounting students. Intellectual intelligence and emotional intelligence were found to have no effect on ethical perceptions of accounting students. Keywords: Intelligence; Love of Money; Ethical Perception.